Silico Study of Alpha-Glucosidase Inhibitory Activity of Triterpenoid Compounds from Ethanol Leaf Extract of Manilkara Kauki - Renita Meilasari; Tukiran Tukiran (Universitas Tadulako, 2025)
Diabetes mellitus type 2 is the most common form of diabetes, characterized by insulin resistance and hyperglycemia. One strategy for managing blood glucose levels is to inhibit the enzyme α-glucosidase, which plays a role in breaking down carbohydrates into glucose. Synthetic inhibitors such as acarbose have been widely used, but they often cause gastrointestinal side effects. Therefore, there is a need to identify alternative inhibitors from safer natural sources. The leaves of Manilkara kauki are known to contain triterpenoid compounds with potential antidiabetic properties. This study aims to evaluate the activity of triterpenoid compounds from the ethanol extract of M. kauki leaves as α-glucosidase inhibitors using an in silico approach via molecular docking. The target protein used was 5NN8, with acarbose as the reference ligand. Docking results showed that two compounds, β1-barrigenol and barringtogenol C, exhibited good binding affinity with energy values of -7.74 and -7.75 kcal/mol, respectively. Both compounds were also able to interact with essential residues at the active site of α-glucosidase, such as ASP616, ARG281, MET519, and TRP376. These results indicate that triterpenoids from Manilkara kauki have the potential as natural α-glucosidase inhibitor candidates.